PROBLEMATIKA PEMBELAJARAN GEOMETRI ANALITIK PADA MAHASISWA PENDIDIKAN MATEMATIKA - Novitasari, Pratiwi (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2025)
This research aims to identify learning problems in analytical geometry courses among mathematics education students. This research uses a meta-analysis method by analyzing 5 articles from educational research journals which discuss analytical geometry problems for students in the Mathematics Education study program. The problem used in this research is student errors in working on analytical geometry problems. Problems with learning analytical geometry among students in mathematics education study programs include student errors in solving problems related to analytical geometry. These errors include errors of fact, conceptual errors, errors in strategy formulation, and calculation errors.